PENGARUH PENAMBAHAN UREA DAN AMONIUM KARBONAT PADA PEREKAT UREA FORMALDEHIDA TERHADAP EMISI FORMALDEHIDA DAN KETEGUHAN REKAT TRIPLEKS JABON - Paribotro Sutigno; Adi Santoso Santoso (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
The problem in using plywood bonded with urea formaldehyde (UF) is formaldehyde emission, especially in a room with limited ventilation. To reduce formaldehyde emission, the glue can be mixed with catching agent. In this paper the effect of urea and ammonium carbonate as catching agent on formaldehyde emission and on bonding strength of UF bonded three plies made from jabon is discussed.The effect of catching agent type on formaldehyde emission is not significant while the effect of percentage of catching agent is highly significant on formaldehyde emission. The higher percentage of catching agent, the lower formal dehyde emission of plywood.The effect of type and percentage of catching agent on plywood bonding strength is highly significant. The higher percentage of catching agent, the lower plywood bonding strength.To meet formaldehyde emission of 0,165 µg/ml it is recomended to use urea 14% on the weight basis of liquid UF. The bonding strength of this plywood conforms with the Japanese standard, 1973.